A Review On Citrus tristeza virus (CTV) And Its Management Approaches - Sachin Sharma (Turkish Journal of Agriculture: Food Science and Technology)
Citrus tristeza virus (CTV), one of the casual agents of citrus decline, is responsible for the death of millions of citrus trees and reduced production and productivity of citrus orchards worldwide. CTV epidemics has been recorded from several parts of the world where mainly steam pitting (SP) and quick decline (QD) strains of CTV have induced severe disease reactions. Identification and characterization of CTV isolates primarily has been focused on the biological assaying in indicator plants, serology-based ELISA and molecular PCR tests. Controlling the presence and spread of CTV where it is absent or establishment is limited heavily relies upon preventive measures, quarantine and legislations. Cross protection is an appealing technique especially for controlling CTV – Stem Pitting strains and use of CTV resistant rootstocks largely prevent infection by CTV – Quick Decline strains. More reliable and effective way to control CTV is breeding for resistant or tolerant cultivars. Advances in molecular biology have lead scientists to find out genes and map genetic loci of CTV resistant citrus and related species that could be exploited in breeding. However incorporation of resistant ability offered by a handful of citrus and its related species into the susceptible cultivars containing other desirable agronomical traits is challenging through classical plant breeding approaches. The following review work is based on Citrus tristza virus and its management practices.